Characteristics of Barlin Banana Velva (Musa acuminata) With the Addition of Katuk Leaf Extract (Sauropus androgynus (l.) merr) And CMC Concentration - Ulya Sarofa; Jariyah; Ken Ratri Dyah Palupi (Nusantara Science and Technology Proceedings, 2023)
Barlin banana contain high nutrients but are not widely processed. Barlin banana velva with the addition of katuk leaf extract will produce a frozen dessert product that is high in nutrition. The addition of CMC (carboxy methyl cellulose) is expected to improve the physicochemical properties of the Velva. This research aimed to determine the effect of katuk leaf extract addition and CMC concentration on the physical, chemical, and organoleptic characteristics of barlin banana velva. This research used a Completely Randomized Design factorial pattern of two factors. Factor I was the addition of katuk leaf extract (2%, 4%, and 6%) and factor II was the concentration of CMC (0.5%, 0.6%, and 0.7 %). The data obtained was then analyzed using analysis of variance, if there were differences, it was continued with the Duncan test (DMRT). The results showed that the best treatment was on the addition of katuk leaf extract 6% and the concentration of CMC 0.5 % which produced barlin banana velva with water content of 70.76%, total solids 29.21%, antioxidant activity 29.15%, total phenols 1.007 mg TAE/g, vitamin C 35.49 mg/100gr, overrun 19.76%, melting time 19.33 minutes, and viscosity 2.16 Pa.s, hedonic organoleptic tests include taste 3.241 (liked a bit), aroma 3.068 (liked a little), texture 3.860 (like), and color 3.724 (like).